2020
DOI: 10.24179/kbbbbc.2020-73470
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-Evoked Myogenic Potential Findings in Patients with Unilateral Idiopathic Sudden Sensorineural Hearing Loss

Abstract: We investigated vestibular function in patients with unilateral idiopathic sudden sensorineural hearing loss (ISSNHL) and vertigo, and assessed the relationship between hearing loss grade and cervical vestibular-evoked myogenic potentials (cVEMPs) and ocular VEMP (oVEMPs) findings. Material and Methods: The study included 31 patients diagnosed with unilateral ISSNHL and vertigo, and 26 healthy individuals (control group) with VEMP. In all participants, pure tone audiometry was used to assess the hearing thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In c-VEMP responses, we found that the n23 latency value in the right ear was the highest in the control group and lower in the patient groups. Furthermore, the latency of p13 for the left ear was highest in the outpatient group and lowest in the inpatient 15 Since the beginning of the COVID-19 pandemic, case reports, reviews, brief clinical reports, and a limited number of clinical studies have been published on audiovestibular symptoms such as vertigo, tinnitus, and hearing loss in COVID-19 positive individuals. Aljasser et al reported that the number of patients suffering from recognizable alterations in auditory symptoms was low and they could not find a statistically significant difference between COVID-19 patients and controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In c-VEMP responses, we found that the n23 latency value in the right ear was the highest in the control group and lower in the patient groups. Furthermore, the latency of p13 for the left ear was highest in the outpatient group and lowest in the inpatient 15 Since the beginning of the COVID-19 pandemic, case reports, reviews, brief clinical reports, and a limited number of clinical studies have been published on audiovestibular symptoms such as vertigo, tinnitus, and hearing loss in COVID-19 positive individuals. Aljasser et al reported that the number of patients suffering from recognizable alterations in auditory symptoms was low and they could not find a statistically significant difference between COVID-19 patients and controls.…”
Section: Discussionmentioning
confidence: 98%
“…Today, VEMP tests are an essential component of the vestibular measurement battery and maintain a clinical evaluation of frequent vestibular diseases, including Meniere’s disease, vestibular neuritis, and superior canal dehiscence syndrome. 15 …”
Section: Discussionmentioning
confidence: 99%